The Influence of Entrepreneurship Competency and Leadership Challenge to Principals’ Leadership Solutions - Kadek Arief Jayadie Putra; Mochamad Bruri Triyono; Rihab Wit Daryono (Universitas Pendidikan Ganesha, 2022)
Education should be able to produce competent human resources. In the era of the industrial revolution 4.0 and 21st-century learning, ahead of vocational school is expected to be increasingly able to diversify educational leadership in all learning activities in the school. Therefore this study aims to analyse entrepreneurial competencies, leadership challenges, and leadership solutions for vocational high school principals in the era of the industrial revolution 4.0 and 21st-century learning. This research is correlational research using ex-post facto research. The sample of this study was 35 respondents who were determined using the purposive sample method. Respondents included school principals, deputy principals, heads of expertise programs, and vocational school teachers. Data collection techniques are used questionnaires. The analysis prerequisite test is done by normality test, linearity test and multicollinearity test. The results obtained that the entrepreneurial competence of the principal (86.91%) is in the very good category, the principal's leadership challenges (83.48%) are in the high category, and the principal's leadership solutions (84.49%) are included in the appropriate category. There is a significant influence between entrepreneurial competence and the principal's leadership solution with a correlation coefficient of 0.374. There is a significant influence between leadership challenges and the principal's leadership solution with a correlation coefficient of 0.806, and there is a significant effect between entrepreneurial competence and the principal's leadership challenge with a regression coefficient of 0.9 or a determinant factor of 81%.